Revenue Management in Service Organizations - Maguire, William (Business Expert Press, 2010)
Ebook from IG Library ; Introduces new ideas such as yield management, while uniting previous subjects such as project management, capacity costing, and the theory of constraints. This book places revenue management at the forefront of management accounting with cost management and performance measurement in supporting roles.